Controlled-Coupling of Quinone Monoacetals by New Activation Methods: Regioselective Synthesis of Phenol-Derived Compounds - Kamitanaka, Tohru; Morimoto, Koji; Dohi, Toshifumi; Kita, Yasuyuki (Synlett, 2019)
We have studied for a long time the reaction of quinone acetal type compounds, such as quinone monoacetals, quinone O,S-acetals, and iminoquinone monoacetals, and have reported the regioselective introduction of various nucleophiles. Quinone monoacetals show various types of reactivities toward nucleophiles due to their unique structures. In this study, we found that aromatic and alkene nucleophiles can be regioselectively introduced into the α-position of the carbonyl group on quinone monoacetals by specific activation of the acetal moiety. These reactions enabled the metal-free synthesis of highly functionalized aromatic compounds by the regioselective introduction of nucleophiles. In this account, we describe our recent studies of the coupling of quinone monoacetals.1 Introduction2 Regioselective Introduction of Aromatic Nucleophiles into α-Position of Carbonyl2.1 Biaryl Synthesis by Introduction of Aromatic Nucleophiles2.2 Synthesis of Terphenyls and Oligoarenes by Iterative Coupling2.3 Synthesis of Phenol Cross-Coupling Products3 [3+2] Coupling with Alkene Nucleophiles3.1 Development of Efficient [3+2] Coupling3.2 Improvement of Brønsted Acid Promotor4 Synthesis of α-Aryl Carbonyl Compounds Triggered by Silyl Transfer5 Utilization of o-Quinone Monoacetals6 Application to Iminoquinone Monoacetals7 Conclusion
Keywords: quinone monoacetal; coupling; biaryl synthesis; terphenyl; phenol; dihydrobenzofuran; α-aryl carbonyl